Delayed referral is common even when new‐onset diabetes is suspected in children. A Swedish prospective observational study of diabetic ketoacidosis at onset of Type 1 diabetes. Issue 6 (16th June 2021) - Wersäll, Johan H.; Adolfsson, Peter; Forsander, Gun; Ricksten, Sven‐Erik; Hanas, Ragnar
Abstract: Objective: Delayed treatment for new‐onset diabetes Type 1 (T1D) can lead to diabetic ketoacidosis (DKA) with potentially devastating consequences. This prospective observational study aimed to characterize pediatric patients with DKA at hospital admission, regarding parental awareness of diabetes‐related symptoms and delayed referrals from primary health care providers to pediatric emergency wards. Research Design and Methods: Patients 0–18 years admitted to hospital with new‐onset T1D and DKA between 2015 and 2017 were invited to participate. Questionnaires were filled out separately by the caregivers and by the attending hospital staff. Data from the Swedish National Diabetes Registry (SWEDIABKIDS) were used for comparison. Delayed referral was defined as a primary healthcare contact due to diabetes‐related symptoms 0–4 weeks before hospital admission without immediate referral, or registered elevated glucose levels at primary healthcare centers without immediate referral. Results: The study included 237 patients, among which parental suspicion of new‐onset diabetes before healthcare contacts was reported in 39%. Parental suspicion of diabetes was associated with higher pH values at diagnosis. Patients in contact with primary health care providers before hospital admission had a delayed referral in 43% of the cases. Delayed referral was associated with lower pH values at hospital admission. Symptoms leading to primary healthcare contacts were similar regardless of whether delay occurred or not. Conclusions: Parental suspicion of diabetes was associated with milder DKA at hospital admission. Delayed referral was seen in a considerable proportion of children with primary healthcare contacts for symptoms associated with diabetes. Increased awareness of diabetes symptoms is of paramount importance.